Perceraian Dengan Alasan Disfungsi Seksual Menurut Hukum Islam - Musaad, Faly Antary; Latupono, Barzah; Fataruba, Sabri (PATTIMURA Law Study Review, 2024)
ABSTRACT: Marriage is a meeting between 2 (two) people with various characteristics, but in a household there are definitely problems that can lead to divorce. Divorce occurs due to separate reasons, including violence or physical defects experienced and in fact divorce can be carried out due to sexual dysfunction. Sexual dysfunction refers to various problems or disorders affecting a person's ability to feel satisfaction or function well in sexual activity, a condition where a person has difficulty having sexual relations with their partner. Several sub-problems or research questions are: 1) What are the procedures and reasons for divorce according to Islamic law? 2) Can the consequences of sexual dysfunction be used as a reason for divorce? This research aims to find out and explain the procedures and reasons for divorce as well as to find out and explain sexual dysfunction as a reason that results in divorce according to Islamic law. The research method used is normative juridical, using a statutory approach, conceptual approach and case approach. The laws used are literature studies, journals, internet media. The research results show that there are 2 (two) divorce procedures according to Islamic law, namely talak divorce and contested divorce. Divorce talak is a husband's vow before a Religious Court which is one of the reasons for the dissolution of a marriage, where the decision has permanent legal force, while divorce is contested as regulated in Government Regulation no. 9 of 1975, namely a divorce lawsuit filed by the wife or her attorney to the court whose jurisdiction includes the defendant's residence. Apart from that, if seen from an Islamic perspective in relation to the wife as the applicant, there is also the term khulu' or khuluk, namely a request for divorce by the wife to the husband in the Religious Court with the condition of giving a ransom or iwadl to and with the consent of her husband. Meanwhile, the reason for divorce is due to sexual dysfunction, both according to the explanation of Article 39 paragraph (2) of the Marriage Law and Article 116 of the Compilation of Islamic Law which sound the same, where one of the reasons that can be used as a basis for divorce is that one of the parties or partners has a disability. serious illness or illness resulting in the inability to carry out their obligations as husband and wife, however the judge must obtain evidence that the defendant is experiencing sexual dysfunction or is impotent.